Evaluation of optical imaging agents in a fluorescence-guided surgical model of head and neck cancer. (June 2018) - Prince, Andrew C.; Moore, Lindsay S.; Tipirneni, Kiranya E.; Ramesh, Tushar; Limdi, Mihir A.; Bevans, Stephanie L.; Walsh, Erika M.; Greene, Benjamin; Rosenthal, Eben L.; Warram, Jason M.
Abstract: Background: Tumor proliferation often occurs from pathologic receptor upregulation. These receptors provide unique targets for near-infrared (NIR) probes that have fluorescence-guided surgery (FGS) applications. We demonstrate the use of three smart-targeted probes in a model of head and neck squamous cell carcinoma. Methods: A dose escalation study was performed using IntegriSense750, ProSense750EX, and ProSense750FAST in mice (n = 5) bearing luciferase-positive SCC-1 flank xenograft tumors. Whole body fluorescence imaging was performed serially after intravenous injection using commercially available open-field (LUNA, Novadaq, Canada) and closed-field NIR systems (Pearl, LI-COR, Lincoln, NE). An ex vivo, whole-body biodistribution was conducted. Lastly, FGS was performed with IntegriSense750 to demonstrate orthotopic and metastatic disease localization. Results: Disease fluorescence delineation was assessed by tumor-to-background fluorescence ratios (TBR). Peak TBR values were 3.3 for 1 nmol ProSense750EX, 5.5 for 6 nmol ProSense750FAST, and 10.8 for 4 nmol IntegriSense750 at 5.5, 3, and 4 d post administration, respectively. Agent utility is unique: ProSense750FAST provides sufficient contrast quickly (TBR: 1.5, 3 h) while IntegriSense750 produces strong (TBR: 10.8) contrast with extended administration-to-resection time (96 h). IntegriSense750 correctly identified all diseased nodes in situ during exploratory surgeries. Ex vivo, whole-body biodistribution was assessed by tumor-to-tissue fluorescence ratios (TTR). Agents provided sufficient fluorescence contrast to discriminate disease from background, TTR>1. IntegriSense750 was most robust in neural tissue (TTR: 64) while ProSense750EX was superior localizing disease against lung tissue (TBR: 13). Conclusion: All three agents appear effective for FGS.